Letter from James Curtis Booth to A. L. Snowden, April 20, 1882 - Booth, James Curtis (1882)
James Curtis Booth (1810-1888) writes to Archibald Loudon Snowden (1835-1912), Superintendent of the United States Mint at Philadelphia from 1879 to 1885, to compare the Philadelphia Mint's method for melting bars with the methods used at the Royal Mint in Bombay, India.
Keywords: Booth, James Curtis, 1810-1888; Snowden, Archibald Loudon, 1835-1912; United States Mint; Mint of the United States; Great Britain. Royal Mint; Smelting